Estimation of Erosion Rate in a Hydrographic Basin in a Deforestation Area in the Brazilian Amazon, Eastern Mato Grosso (Journal of Asian Geography, 2024)
The central region of Brazil, geographically located in Mato Grosso, presents changes in land cover with replacement of the forest for soybean and cotton cultivation, intensifying soil losses in a hydrographic basin located in the tropical climate. The objective of the research is to estimate the loss of soil in the Curisevo River Basin, from the Universal Soil Loss Equation. The methodologies used were the elaboration of a cartographic base in the QGIS geographic information system, with the spatial information of slopes, soil types and land cover, of the Curisevo River Basin. The rainfall erosivity was estimated with rainfall data from the National Institute of Meteorology and the erodibility of the soils was estimated according to the indications of the State of Mato Grosso. The land cover of the Curisevo River Basin was analyzed based on remote sensing images with the vectorization of the areas of the agriculture, pasture and forest classes. The spatial data of slopes of the Curisevo River Basin were obtained from the Shuttle Radar Topography Mission base, with spatial analysis treatment in QGIS. In the basin with an area of 1.18 million hectares, an erosion rate of 134,526 t/ha/year was estimated, corresponding to 16 million tons of sediments. This study contributes to the geographical studies, and the indices used in the equation to estimate soil losses can be analyzed by climatic, pedological, geomorphological and landscape analysis studies in land cover changes in a watershed.